Réponses

  • Utilisateur Brainly
2014-03-21T17:49:42+01:00
On développe :
f(x)=6x²-7x+1-8x²-4x+2
     =(6-8)x²+(-7-4)x+3
     =-2x²-11x+3

on factorise :
f(x)=-2(x+11/4)²+145/8
f(x)=-2(x+11/4)²+145/8 n'est pas une forme factorisée (pas grave, ce n'était pas demandé). :):)
Meilleure réponse !
2014-03-21T17:51:06+01:00
6x² - 7x + 1 - 8x² - 4x + 2 = 6x² -8x² - 7x - 4x + 1 + 2
                                     = (6x² - 8x²)- (7x + 4x) + (1 + 2) 
                                     =  -2x² - 11x + 3